Development of Learning Media Assisted by Android Studio to Explore Mathematical Ability of Junior High School Students - Erni Puji Astuti; Riawan Yudi Purwoko; Adi Amin Gunawan (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2021)
This study aims to determine the development procedure and feasibility of learning media for mathematics assisted by the android studio to explore the mathematical abilities of seventh-grade junior high school students. This type of research is research and development (RD). The model used is a 4-D model. The stages of the 4-D model consist of defining, designing, developing, and disseminating. The instruments used are validation sheets and questionnaires. The data analysis technique used is in the form of qualitative descriptive analysis. The validation results obtained from material experts obtained an average of 3.57 with very valid criteria, media experts got an average of 3.66 with very valid criteria, and large group trials obtained a percentage of 72.49% with practical criteria. Based on the product development stages and the criteria that have been set, the mathematics learning media assisted by the android studio is declared valid and practical and can be used as a reference to explore students' mathematical abilities because the products developed are focused and have strong characteristics.